2014
DOI: 10.1186/1556-276x-9-227
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of undoped and indium-doped thermoelectric lead telluride nanoparticles

Abstract: Undoped and indium (In)-doped lead telluride (PbTe) nanostructures were synthesized via solvothermal/hydrothermal route. The crystalline structure of the as-prepared undoped and In-doped PbTe samples was examined by X-ray diffraction (XRD) which indicated the formation of face-centered single-phase cubic crystal. A first principle calculation on indium doping shows that the indium atoms are more likely to replace lead (Pb) rather than to take the interstitial sites. Laser-induced breakdown spectroscopy (LIBS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Further strong intense peaks and other weak peaks are also indexed in the XRD pattern matching with the corresponding JCPDS file. The observed peaks were well matched with the XRD of undoped PbTe synthesized by solvothermal/hydrothermal process [58]. With the XRD of maximum yield sample A4 shows the formation of PbTe and reveals an average crystallite size of 36 nm for the A4 sample (Table 1).…”
Section: Structural Analysissupporting
confidence: 75%
“…Further strong intense peaks and other weak peaks are also indexed in the XRD pattern matching with the corresponding JCPDS file. The observed peaks were well matched with the XRD of undoped PbTe synthesized by solvothermal/hydrothermal process [58]. With the XRD of maximum yield sample A4 shows the formation of PbTe and reveals an average crystallite size of 36 nm for the A4 sample (Table 1).…”
Section: Structural Analysissupporting
confidence: 75%
“…More and more attentions have been paid to the bulk nanostructured thermoelectric materials due to their high thermoelectric performances [ 1 5 ]. Tang et al reported the layer nanostructured Bi 2 Te 3 bulk materials sintered by spark plasma sintering and combined melt spinning technique, and obtained the highest ZT value of 1.35 at 300 K [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6(a) shows XRD diffraction patterns recorded for PbTe precursor matched with the one in the literature, which can attributed to a face-centered cubic PbTe phase (JCPDS: 78-1905)[26]. The diffraction peaks in the XRD patterns of the synthesised precursor (CH 3 NH 3 I) are shown inFigure 6(b), can be indexed as a Tetragonal phase (JCPDS: 00-010-0737) which confirms the crystalline phase pure of the as-synthesized CH 3 NH 3 I.…”
mentioning
confidence: 55%